BIMOS transistor solutions for ESD protection in FD-SOI UTBB CMOS technology. (January 2016) - Galy, Philippe; Athanasiou, S.; Cristoloveanu, S.
Abstract: We evaluate the Electro-Static Discharge (ESD) protection capability of BIpolar MOS (BIMOS) transistors integrated in ultrathin silicon film for 28 nm Fully Depleted SOI (FD-SOI) Ultra Thin Body and BOX (UTBB) high- k metal gate technology. Using as a reference our measurements in hybrid bulk-SOI structures, we extend the BIMOS design towards the ultrathin silicon film. Detailed study and pragmatic evaluations are done based on 3D TCAD simulation with standard physical models using Average Current Slope (ACS) method and quasi-static DC stress (Average Voltage Slope AVS method). These preliminary 3D TACD results are very encouraging in terms of ESD protection efficiency in advanced FD-SOI CMOS.